2014
DOI: 10.1021/ie5031985
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Covalent-Functionalized Graphene Oxide with Polymer and Reactive Compatibilization on Thermal Properties of Maleic Anhydride Grafted Polypropylene

Abstract: The covalent functionalization of graphene oxide(GO) with bis(3-aminopropyl)-terminated poly(ethylene glycol)(NH 2 -PEG-NH 2 ) and then the grafting with maleic anhydride grafted polypropylene (MAPP) oligomer matrix using reactive compatibilization were carefully analyzed and verified through detailed investigations. Improvements in the compatibility among the modified GO and matrix, thermal stability, flame property, and crystallization property were achieved through the addition of a small amount of GO graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 66 publications
0
35
1
1
Order By: Relevance
“…The large increase in this ratio also is associated with an excess of defects in the graphitic lattice and a decrease in the average size of the in‐plane sp2 domain. These defects could be associated with the interactions between GO and amine groups of compatibilizer and also with the partial thermal reduction during solution blending . It also can be seen that M‐PP/PPgDMAE‐15/GO‐1.0 sample shows a lower increase in this ratio compared with the solution samples this indicates a more pronounced reduction of GO during melt mixing at high PP processing temperatures.…”
Section: Resultsmentioning
confidence: 89%
“…The large increase in this ratio also is associated with an excess of defects in the graphitic lattice and a decrease in the average size of the in‐plane sp2 domain. These defects could be associated with the interactions between GO and amine groups of compatibilizer and also with the partial thermal reduction during solution blending . It also can be seen that M‐PP/PPgDMAE‐15/GO‐1.0 sample shows a lower increase in this ratio compared with the solution samples this indicates a more pronounced reduction of GO during melt mixing at high PP processing temperatures.…”
Section: Resultsmentioning
confidence: 89%
“…The covalent-functionalized GO with polyethylene glycol have been reported in our previous research [16]. In this work, three chain lengths of double amino-terminated polyethylene glycol (NH 2 -PEG-NH 2 ) were used to functionalize graphene and were investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Bozlar M. et al first observed the percolation of CNT in which the l had an enhancement of 130% (0.4 W m À1 K À1 ) at 0.15 wt% CNT loading (totally, B0.75 wt% of Al 2 O 3 -CNT hybrid filler) in epoxy matrix. [15][16][17][18][19][20] The l of polyamide (PA) composites was increased by 112% at 10 wt% graphene oxide loading via the in situ polymerization coupled with the thermal reduction method. An important reason probably rests in the predominance of interface thermal resistance (ITR) between the graphene layers and polymer matrix, and another one is that, in many cases, no efficient thermal conductive networks are constructed.…”
Section: Introductionmentioning
confidence: 99%